Evaluating the effects of the World Health Organization's online intervention ‘iSupport’ to reduce depression and distress in dementia carers: a multi-centre six-month randomised controlled trial in the UKResearch in context - Gill Windle; Greg Flynn; Zoe Hoare; Nia Goulden; Rhiannon Tudor Edwards; Bethany Anthony; Patricia Masterson Algar; Suman Kurana; Aimee Spector; Gwenllian Hughes; Ryan Innes; John Connaghan; et al. (The Lancet Regional Health. Europe)
Summary: Background: Sustaining the capabilities of dementia carers is a global priority. ‘iSupport’ is a self-guided online intervention designed by the World Health Organization (WHO) to reduce mental health problems in dementia carers. iSupport is undergoing global implementation, however there is an absence of effectiveness evidence. This study tested the effectiveness of iSupport to reduce distress and depression in dementia carers. Methods: A pragmatic randomised controlled trial was conducted in three centres. Adult carers (18+) living in the community were recruited in England, Wales and Scotland and randomly assigned (1:1) through a web-based system to iSupport or usual care. Outcome assessors were masked to allocation. The primary outcomes assessed the difference in distress and depression between baseline and six-months. The target sample size was 350 to enable 90% power, significance at 2.5% including 25% attrition (262 completers) on either outcome. Analysis followed the intention-to-treat (ITT) principle. The trial was registered with ISRCTN registry (17420703). Findings: Between 12th November 2021 and 31st March 2023,177 carers (50.3%) were randomised to usual care and 175 (49.7%) to iSupport. 263 (74.7%) completed the trial. All were included in the ITT analysis. Mean distress scores at six-months were 20.0 (SD = 8.3) for usual care and 20.6 (SD = 8.6) for iSupport. The mean difference was 0.16 (95% CI −1.17 to 1.49, p = 0.29) after adjusting for covariates. Mean depression scores at six-months were 9.5 (SD = 7.0) for usual care and 9.8 (SD = 6.5) for iSupport. The mean difference at six-months was −0.54 (95% CI = −1.70 to 0.62, p = 0.44). No serious adverse events were linked to the trial. Interpretation: To our knowledge this is the largest trial evaluating a self-guided online intervention in UK dementia carers, and the first to successfully evaluate the effectiveness of iSupport. The null findings are significant given the ongoing global implementation of iSupport by the WHO and the adoption of self-guided interventions into mainstream care delivery as part of digital health transformations. Funding: NIHR.